Winter willpower - Yu, Bill (Survive! (Graphic Planet (Firm)), 2020)
Competitive snowboarders Terence and David are up on the slopes when Terence's desperation to nail a trick sparks an avalanche which traps the two boys. Includes true survival stories, a survival guide, critical thinking question, trivia, and a glossary.